THE ELDERLY PERSON: : THE PERCEPTION ABOUT SEXUALITY AND WELL-BEING - Germania da Silva, Bianca; Paixão da Silva, Dalila; Gomes da Conceição Santana, Mônica (Health and Society, 2021)
This article aimed to answer the following research problem: how does the perception of sexuality in the aging process affect the psychosocial well-being of the old person? Thus, the general objective was to analyze how the perception of sexuality in the aging process affects the psychosocial well-being of the old person. The research method of systematic literature review was used, using indicators such as elderly, sexuality, perception, psychosocial and well-being. Google Scholar, Scielo and BDTD were used as a database plataform. We included articles and dissertations dating from 2010 to 2020 that addressed the theme: sexuality of the older person. Forty-three articles were found in which only 5 we used. The article and dissertations presented questions related to the elderly perception about their sexuality, the importance of sexual education and the experience of the well-being of the elderly, also exhibited the experience of some elderly person. Therefore, it is concluded that there is a need for more research aimed at exploring the perception of the elderly about their sexuality and how it affects them. It is expected that this theme can be expanded with research aimed at guiding and expanding knowledge and learning about sexuality in the elderly phase, seeking to highlight the importance of the autonomy of the old person over their choices in face of the possibilities of experiencing their sexuality.